"Assessing the Intersectional Impact of Domestic Migration Law - Sarkin, Jeremy Julian (2024)
In 2020, the Israeli Supreme Court held section 4 of the Law on Prevention of Infiltration and Ensuring the Departure of Infiltrators from Israel, also known as the Deposit Law, to be unconstitutional. Among other provisions, that law required 36 per cent of the wages of foreign workers to be paid into a dedicated account and returned when the person left the country. For years the Deposit Law had a negative impact on the lives of asylum seekers because of its racialised, gendered, ethnonational and religious impact. Its intersectional impact illustrates cultural, structural and systematic violence, which has been particularly punitive for asylum-seeking women, who are more exposed to sexual and gender-based violence (SGBV). In this context, this interdisciplinary qualitative and empirical research article draws from empirical fieldwork conducted in Israel to understand the intersectional impact of the law. It therefore conducts a theoretical examination of the literature and connects that to the empirical study. Thus, the article empirically and theoretically investigates (i) the extent to which state-created categories foster unlawful multilayered and multilevel forms of vulnerability and discrimination; (ii) the intersectional impact of the Deposit Law and how it is related to SGBV; and (iii) how state-created intersecting vulnerabilities can be diagnosed. The overall goal of the article is to indicate the intertwined nature and interconnection between state-created categories and the inevitability of state-created vulnerabilities.